A road embankment on soft clay: field behaviour and prediction - Ali, F.H.; Hashim, Roslan (1991)
Even though studies on the behaviour of embankments on soft clay have now been for more than twenty five years, there are still a number of uncertainties in their behaviour. This paper describes the finite element analyses carried out on 3m embankment on soft clay which was instrumented with settlement gauges, piezometers and inclinometers.